How to win on the battlefield the 25 key tactics of all time - Johnson, Robert 1967-; Whitby, Michael; France, John (Thames & Hudson, 2010)
"In this book we examine and then analyse, through a series of case studies, 25 of the most important tactics used in war on land, at sea and in the air. These are illustrated with examples from around the globe and from across history in order to demonstrate the enduring value of each one. While much of the current intellectual debate on war focuses on what is new, or even 'post-modern', we are eager to show that, despite obvious changes in weaponry, technology and mobility, certain key techniques and principles have been applied with equal success in the military encounters of the past and are still relevant today. Since so many works of military history focus narrowly on the West, we have selected examples from as wide a field as possible and we have tried to raise awareness of some less well-known battles. Our intention is to highlight the function of each tactical concept in its historical setting"--Preface